Harmonizing Seismic Vulnerability Data for Effective Seismic Risk Assessment: Expert Judgment Method and Findings from a Multi-Stakeholder Study in Indonesia - Adi Setiabudi Bawono; Noram Irwan Ramli; Mohamad Idris Ali (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
Seismic Risk Management (SRM) is crucial for mitigating the impact of earthquakes, encompassing earthquake preparedness, response planning, building design, and emergency management systems. The 2006 Yogyakarta earthquake in Indonesia resulted in significant loss of life, infrastructure damage, and economic impact, underscoring the importance of Seismic Risk Assessment (SRA) for effective risk reduction. Seismic vulnerability functions are commonly used for SRA, but data collection can be expensive and challenging, and results may be biased due to expert judgment. In Indonesia, variability in house damage state definitions among agencies poses challenges in harmonizing data. This study used expert judgment to harmonize differences in damage state variables resulting from variable references. Data on damage states from five (5) agencies were collected and harmonized through input from earthquake engineering experts via online questionnaires. The resulting data identified five (5) types of damage and reduced variables to nine through harmonization. Twenty (20) experts with diverse backgrounds, including academics, researchers, contractors, consultants, volunteers, and government stakeholders, participated in the study through online questionnaires, and the results were processed and analyzed. The expert judgment method successfully harmonized the differences in damage state variables, ensuring a consistent, reliable, and accurate assessment of building damage, particularly housing damage. The findings of this study underscore the crucial role of expert judgment in harmonizing data for seismic risk assessment. The survey gathered input from experts with diverse backgrounds, including government stakeholders and academics, enriched the study's findings and contributed to a comprehensive understanding of earthquake disaster management. Through expert judgment, the study successfully consolidated variables from different agencies into nine (9) harmonized variables for assessing building damage. Furthermore, experts proposed an additional fourteen (14) factors that need to be considered in residential house damage inspection forms, providing critical information for estimating the extent of damage and informing decisions about repairs or demolition. These variables can be categorized into Rapid Visual Screening (RVS) and observation in more detail, aiding in effective earthquake risk management. However, further validation through comparative literature and field analysis is needed to enhance accuracy and adaptability and explore the potential of incorporating soft computational algorithms in seismic vulnerability assessments as a promising approach.